Comparative Study on Breaking Strength of Burnt Clay Bricks Using Novel Based Completely Randomized Design (CRD) - Hussain, Zahid; Ali, Shamshad (Civil Engineering Journal, 2019)
The aim of this study is to present the results of breaking strength tests for burnt clay bricks from various historical deposits. The native clay bricks production technique is the known method of brick making, particularly in South Asian countries. Numerous studies have been conducted on hand-molded formed bricks. The clay bricks that were considered for the comparative study, were made from four different clays sources. Their breaking strength was determined using for examining the maximum load at failure and the effects were investigated subsequently. The basic objective of this experimental study was to compare the breaking strength of locally fired clay bricks using a novel based completely randomized design via a single factor with four levels of clay sources representing the factors. For this purpose, 24 brick samples were made from four different clay sources while the breaking strength of each sample was measured. Pairwise comparison trials, including Duncan’s multiple range, Newman–keuls, Fisher’s least and Tukey’s tests were conducted. Based on experimental investigations, the results revealed that using analysis of variance at 95% CI, the difference in breaking strength between clay source of Hyderabad (A) and Rawalpindi (B), followed by Kohat (C) and Peshawar (D) was significant and also the difference among the means of these clay courses was significant which clearly exposed that the clay site and chemical composition has a great impression of the breaking strength of the burnt bricks.